Relación del componente afectivo con el Rendimiento Académico en estudiantes de optometría de la Universidad Antonio Nariño de Colombia (2022)
Self-Regulated Learning (SRL) as an important factor in the Academic Performance (AR) can be affected by negative responses from test anxiety (AE), describing the process of AE in students can allow us to know the way in which this develops in the population and its influence on the Academic processes